Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes. Issue 5 (4th March 2021) - Prabha, B.; Sini, S.; Sherin, D. R.; Neethu, S.; Rameshkumar, K. B.; Manojkumar, T. K.; Jayamurthy, P.; Radhakrishnan, K. V.
Abstract: Promalabaricone B (PMB), an acylphenol was isolated from dichloromethane-soluble extract of the seeds of Myrisitica fatua Houtt. PMB exhibited significant inhibitory activity on α -glucosidase enzyme. The molecular docking and dynamics studies of PMB with human maltase-glucoamylase were performed. PMB exhibited an enhanced glucose uptake in L6 myotubes with 46.3% in 2.5 µ M. Encouraged with these results; we investigated the molecular mechanism of PMB through the upregulation of AMPK. The results revealed that PMB promoted the glucose uptake in myocytes by stimulating the translocation and expression of GLUT4. From this, it is clear that PMB can acts as a potential therapeutic option for diabetes treatment, and its hypoglycaemic effect may be mediated by AMPK upregulation and induction of GLUT4 translocation. Abstract :